2008
DOI: 10.3892/ijo.32.5.1119
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a nanotechnology-based carrier for delivery of curcumin in prostate cancer cells

Abstract: Abstract.We have initiated studies to enhance targeted delivery of an anticancer agent, curcumin, for prostate cancer treatment by incorporating this agent into the liposomes (nanodelivery vehicles primarily composed of phospholipids) coated with prostate membrane specific antigen specific antibodies. We prepared curcumin-loaded liposomes of various lipid compositions by sonication at an average size of 100-150 nm. Un-entrapped curcumin was removed by size exclusion chromatography. Data show that curcumin pref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
111
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(116 citation statements)
references
References 18 publications
1
111
0
2
Order By: Relevance
“…This result may be associated with the inhibition of proliferation and the induction of apoptosis and cell cycle arrest in endothelial cells in vitro. Liposomal curcumin has been reported to exhibit anti-cancer activity on colorectal cancer (19), prostate cancer (20), head and neck squamous cell carcinoma (21), and pancreatic (22) and cervical cancer (23). In this study, we revealed that liposomal curcumin inhibits tumor growth in the Lewis lung cancer mouse model primarily by targeting tumor angiogenesis.…”
mentioning
confidence: 71%
“…This result may be associated with the inhibition of proliferation and the induction of apoptosis and cell cycle arrest in endothelial cells in vitro. Liposomal curcumin has been reported to exhibit anti-cancer activity on colorectal cancer (19), prostate cancer (20), head and neck squamous cell carcinoma (21), and pancreatic (22) and cervical cancer (23). In this study, we revealed that liposomal curcumin inhibits tumor growth in the Lewis lung cancer mouse model primarily by targeting tumor angiogenesis.…”
mentioning
confidence: 71%
“…Doxorubicin has been the focus of investigation due to the fact that it is one of the most effective first-line anticancer therapeutics developed, but its toxicity in many organs limits its use. [13][14][15][16] Doxil (doxorubicin), the first nanodrug approved by the USA Food and Drug Administration (FDA) in 1995, was based on the work by Barenholz on a liposomal-based doxorubicin formulation. A key concept in developing the doxorubicin-liposomes was the enhanced permeability and retention effect, which results from differences in vasculature between benign and malignant tissue.…”
Section: Therapeutic Applicationsmentioning
confidence: 99%
“…72 In another study, liposome preparations of curcumin exhibited superior antiproliferative and apoptotic effects on six pancreatic cancer cells, and also inhibited pancreatic tumor growth in mouse models. 73 Use of the ionophore method of drug loading allows much higher drug:lipid ratios than the conventional citrate method. 74 This formulation has given excellent results in studies comparing the efficacy of conventional CHOP (chemotherapy treatment composed of cyclophosphamide, doxorubicin, vincristine, and prednisone) and CHOP in which the vincristine has been replaced by LNP-vincristine.…”
Section: 63mentioning
confidence: 99%